Phase field modelling of glacial crevasses subject to meltwater-driven hydro-fracture - Clayton,T; Duddu,R; Siegert,M; Martinez-Pañeda,E (2023)
Surface crevasses are predominately mode I fractures that penetrate tens of metres deep into grounded glaciers and floating ice shelves. However, elevated surrounding temperatures have resulted in the production of surface meltwater, which accumulates in neighbouring crevasses and applies additional tensile stresses to crack walls. This process is known as hydrofracture; and if sufficient, can promote full thickness crevasse propagation, and lead to iceberg calving events. Net ablation of ice sheets has become of great concern, as it has become the largest contributor to sea-level rise. To overcome the limitations of empirical and analytical approaches to crevasse predictions, we here propose a thermo-dynamically consistent phase field damage model to simulate damage growth in both ice sheets and floating ice shelves using the finite element method.The model incorporates the three elements needed to mechanistically simulate hydrofracture of surface and basal crevasses: (i) a constitutive description of glacier flow, incorporating the non-linear viscous rheology of ice using Glen’s flow law, (ii) a phase field formulation capable of capturing cracking phenomena of arbitrary complexity, such as 3D crevasse interaction, and (iii) a poro-damage mechanics representation to account for the role of meltwater pressure on crevasse growth. To assess the suitability of the method, we simulated the propagation of surface and basal crevasses within grounded glaciers and floating ice shelves and compared the predicted crevasse depths with analytical methods such as linear elastic fracture mechanics and the Nye zero stressmethod, with results showing good agreement for idealised conditions.ReferencesT. Clayton, R. Duddu, M. Siegert, E. Martínez-Pañeda, A stress-based poro-damage phase fieldmodel for hydrofracturing of creeping glaciers and ice shelves, Engineering Fracture Mechanics272 (2022) 108693